Regulation Mechanism of Virulence in Edwardsiella piscicida by UvrY ‐ BarA Two‐Component System in Response to Environmental Formate and Acetate Signals - Benqiang Li; Yujuan Hong; Xiaomei Cai; Wen Si; Shuai Shao; Huili Liu; Kaiyu Yin (Journal of Fish Diseases, 2026)
Edwardsiella piscicida is a common marine pathogen infecting diverse fish species, causing hemorrhagic septicemia and substantial economic losses to the global aquaculture industry. The hemolysin proteins (EthA) and type III and VI secretion systems (T3SS/T6SS), controlled by the EsrA‐EsrB two‐component system (TCS), are essential for bacterial colonisation and host invasion. This study demonstrates that the UvrY‐BarA TCS negatively regulates the expression of esrB , subsequently activates the expression of hemolysin proteins, and inhibits the secretion of T3SS/T6SS proteins. Importantly, when it detects environmental formate and acetate signals, the UvrY‐BarA TCS controls virulence gene expression, affecting the colonisation ability of E. piscicida in turbot. In summary, our findings reveal a novel role for the UvrY‐BarA TCS in mediating the regulatory effects of formate and acetate signals on bacterial virulence, providing deeper insights into the pathogenesis of E. piscicida .